2009
DOI: 10.4319/lom.2009.7.751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CHN analysis and Hach acid digestion to quantify total nitrogen in marine organisms

Abstract: The quantification of total nitrogen in biological samples has wide applications in marine sciences. Different methods are currently used to quantify nitrogen content, but their accuracies have not been extensively tested with samples of marine origin. In this study, we compared results for total nitrogen analysis generated by the Hach method, a relatively new and low-cost technique, with CHN elemental analysis, a widely accepted and costly technique. Sixty aquatic organisms were tested covering substantial bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…The range of values, 2-10% nitrogen for sponges in this study, encompasses the 6% nitrogen found in other sponges, such as Hymeniacidon heliphila (Barbarino and Lourenco, 2009) and Spongilla lacustris (Sandjensen and Pedersen, 1994). S. lacustris also had a carbon content (30%) within the range of those found in the current study (9-41%).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The range of values, 2-10% nitrogen for sponges in this study, encompasses the 6% nitrogen found in other sponges, such as Hymeniacidon heliphila (Barbarino and Lourenco, 2009) and Spongilla lacustris (Sandjensen and Pedersen, 1994). S. lacustris also had a carbon content (30%) within the range of those found in the current study (9-41%).…”
Section: Discussionsupporting
confidence: 56%
“…CHN values obtained for sponges in the current study were at the lower end of those recorded in marine ectotherms (Barbarino and Lourenco, 2009;Obermüller et al, 2013). The range of values, 2-10% nitrogen for sponges in this study, encompasses the 6% nitrogen found in other sponges, such as Hymeniacidon heliphila (Barbarino and Lourenco, 2009) and Spongilla lacustris (Sandjensen and Pedersen, 1994).…”
Section: Discussionmentioning
confidence: 77%
“…The animals were grouped by their respective taxonomic phyla, but many species that belong to different orders or classes of a same phylum were analyzed. Thus, within the same phylum, part of the variations in chemical profiles can be assumed as a consequence of phylogenetic traits (Barbarino & Lourenço, 2009). It is also important to point out that our results are expressed as percentage of substance to the total mass, thus the occurrence of large amounts of structural inorganic contents contribute to diminish the tissue concentrations of nitrogen and all other substances measured here (phosphorus, protein, carbohydrate, and lipid).…”
Section: Gross Chemical Profile General Pointsmentioning
confidence: 99%
“…In contrast to protein analysis, total nitrogen (TN) is relatively simple to measure, and it is very accurate (Barbarino & Lourenço, 2009). For virtually all species chemically known, most of the nitrogen content is found in proteins, which means that both total protein and TN tend to vary in a proportional fashion (Huet et al, 1988;Mariotti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation